Fertility Narratives: An Experimental Project of Applied Anthropology within a Fertility Clinic of Southern California - Guerzoni, Corinna Sabrina (AM. Rivista della Società Italiana di Antropologia Medica, 2021)
Fertility Narratives: An Experimental Project of Applied Anthropology within a Fertility Clinic of Southern California The article presents an experimental project of applied anthropology realized within WeHo Fertility Center (whfc), a fertility institute of Southern California (2017-2020). Since infertility was almost never described as a disease by doctors and patients, I proposed the concept of fertility narratives, a notion mainly inspired by illness narratives of Kleinman, to refer to a set of narratives relating to the temporal, emotional and biopolitical stratification of reproductive paths. In this article, I will focus only on the reproduction temporal stratification, showing three different scopes which emerged during the lab: body temporality, staff temporality and patients’ temporality. Fertility Narratives: un progetto sperimentale di antropologia applicata all’interno di una clinica di fertilità californiana L’articolo presenta un progetto sperimentale di antropologia applicata realizzato all’interno del WeHo Fertility Center (whfc), un istituto di fertilità della California meridionale (2017-2020). A seguito di un periodo di osservazione presso il centro, ho proposto l’apertura di un laboratorio denominato Fertility Narratives Lab. Poiché l’infertilità non è stata quasi mai descritta come una malattia da medici e pazienti, ho proposto il concetto di narrazioni sulla fertilità, nozione principalmente ispirata alle narrazioni sulla malattia kleinmaniane, per fare riferimento a un insieme di narrazioni relative alla stratificazione temporale, emotiva e biopolitica dei percorsi riproduttivi. In questo articolo mi concentrerò solo sulla stratificazione temporale della riproduzione, mostrando tre diversi ambiti emersi durante il laboratorio: la temporalità corporea, la temporalità del personale e la temporalità dei pazienti.